Strategies for Preventing Radicalism: A Case Study at Pondok Pesantren (Islamic Boarding School) - Bachtra Dona Lubis; Suhirman Suhirman; Kasmantoni Kasmantoni (Jurnal Indonesia Studi Moderasi Beragama, 2025)
Background: This study examines the strategies employed at Pondok Pesantren Makrifatul Ilmi in South Bengkulu to prevent radicalism, a growing concern in educational institutions, especially Islamic boarding schools. Objective: The primary objective is to identify the steps taken by the pesantren to combat radicalization and to assess the factors that support and hinder these efforts. Method: A descriptive qualitative approach was employed to collect data through interviews, observations, and documentation. Result: The findings reveal that the pesantren implements three key strategies: religious functions, educational activities, and social engagement. Supporting factors include heightened student awareness, strong internal cooperation within the pesantren, and active parental involvement. However, the study also highlights several challenges, including students' diverse social backgrounds, varying interpretations of nationalism, and the pervasive influence of technology. Conclusion: While the pesantren's strategies for preventing radicalism are effective, overcoming these barriers requires sustained cooperation and adaptability. Contribution: This research contributes to a deeper understanding of counter-radicalism strategies in pesantren and offers insights into the unique challenges faced by Islamic educational institutions in South Bengkulu.